2003
DOI: 10.1034/j.1600-0692.2003.20619.x
|View full text |Cite
|
Sign up to set email alerts
|

On‐line and off‐line models for the rolling process

Abstract: Rolling is an essential process for the production of plate, strip and foil. Parallel with automation of the rolling mills, there is an increasing demand for improved performance and accuracy of the rolling models for on‐line mill setup and control. This paper discusses recent advances on the development of rolling theories, particularly in non‐traditional rolling regimes, such as rolling of thin hard tin‐plate, temper rolling and foil rolling. Development and implementation of models based on these theories f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…Published reviews on the roll-separation force and the torque can be found in [ 1 ] and more extensively in [ 2 ]. The main problem when solving the roll-separation force and the torque is to calculate the roll-pressure distribution along the angle on the roll, where the rolled steel is in contact.…”
Section: Introductionmentioning
confidence: 99%
“…Published reviews on the roll-separation force and the torque can be found in [ 1 ] and more extensively in [ 2 ]. The main problem when solving the roll-separation force and the torque is to calculate the roll-pressure distribution along the angle on the roll, where the rolled steel is in contact.…”
Section: Introductionmentioning
confidence: 99%
“…Temper rolling is an important rolling process with small reduction in thickness. In recent years, with the increasing demand for improved performance and accuracy of the rolling strip, a number of research work have been done on the temper rolling process [1][2][3][4][5][6][7][8][9]. Chandra and Dixit have studied the deformation field of temper rolling using rigid-plastic finite element method [1].…”
Section: Introductionmentioning
confidence: 99%
“…Zhong indicated that the temper rolling chatter is a self-excited vibration based on a series of tests, and its cause is the rolling interface where partial fluid lubrication and viscous-slip exist [3]. Yuen developed an on-line mill setup and control model used in foil rolling and temper rolling [4]. Larkiola and Myllykoski predicted the mechanical properties of steel strips and temper rolling force by using neural network modeling and measured process data [5].…”
Section: Introductionmentioning
confidence: 99%
“…Os modelos on-line são efetivamente utilizados na operação de plantas industriais, tanto na otimização do processo (cálculo de setups) como no controle em tempo real. Como 52 atesta Yuen (2003), é primordial que tais modelos, ainda que em prejuízo da acurácia, sejam caracterizados pela consistência e por uma formulação matemática eficiente, que permita que seus cálculos sejam realizados no exíguo tempo disponível. Além disso, os modelos on-line devem ser passíveis de inversão, para que sua adaptação possa ser eficientemente executada.…”
Section: Principais Categorias De Modelos Para a Laminação Planaunclassified
“…Segundo Yuen (2003), para que se obtenham produtos de alta qualidade, com a espessura objetivada e boa planicidade, é essencial uma estimativa precisa da força de laminação. Prover tal estimativa é um dos principais objetivos dos modelos de deformação.…”
Section: Premissas E Equações De Um Modelo De Deformaçãounclassified